IL-23 and Th17 cytokines in intestinal homeostasis. - Maloy, K; Kullberg, M (2008)
The discovery of the Th1/Th2 paradigm of CD4(+) T-cell subsets redefined our understanding of immunity by highlighting the essential roles of cytokine networks in the induction and regulation of immune responses. Most recently, the identification of an additional subset, known as Th17 cells, has further illustrated the complexity and diversity of effector CD4(+) T cells. Th17 responses have been closely associated with the cytokine interleukin (IL)-23 and, although originally pinpointed as having a deleterious role in autoimmune tissue pathology, the IL-23/Th17 axis has also been associated with protective immunity at mucosal surfaces. Recent progress has highlighted the heterogeneous nature of Th17 responses, has demonstrated diverse cellular sources for Th17-associated cytokines, and has begun to dissect the individual roles of these cytokines in different disease processes. Here, we will review the evidence linking the IL-23/Th17 axis to chronic intestinal inflammation and also will discuss its beneficial roles in intestinal protection and homeostasis.